PERBEDAAN RISIKO KREDIT BANK UMUM SWASTA NASIONAL DEVISA (BUSN) DAN BANK ASING YANG GO PUBLIC DI INDONESIA - Ira Lailatul Maghfiroh; Nur Khusniyah Indrawati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The research aims to know the difference between credit risk in The Private National Bank and Foreign Bank terms of the value of the Loan to Deposit Ratio (LDR), Non Performing Loan(NPL), Capital Adequacy Ratio (CAR) and Bank Size. This research are explanatory research and used a descriptive comparative method. The period of study are 2007-2011 year. This study includes research in the study population because as all elements of the population are studied. The data used The Private National Bank and Foreign Bank published on the Bank Indonesia and the official website of the bank which is the object of research. The different test performed using an independent sample t test and Mann-Whitney U test.The results for each ratio analysis shows that there is no difference in the level of credit risk in terms of the value of LDR, NPL and Bank Size between The National Private Banks and Foreign Banks in Indonesia. However, in terms of the CAR indicates that the credit risk between the National Private Banks and Foreign Banks are significantly different. Keywords: Credit Risk Management, Loan to Deposit Ratio (LDR), Non Performing Loan(NPL), Capital Adequacy Ratio (CAR), Bank Size, The Private National Bank (BUSN), Foreign Banks.